2017
DOI: 10.1039/c6ra27109j
|View full text |Cite
|
Sign up to set email alerts
|

Investigating microwave deicing efficiency in concrete pavement

Abstract: Microwave deicing is an intelligent and environmentally friendly method that overcomes the many shortfalls of traditional deicing methods, including mechanical, chemical and thermal techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…38,39) The increase in absorbance at 250 nm is attributed to the generation of C-C double bonds. 40) The change in the absorbance of PVC upon X-ray irradiation was negligible on the coloring due to the oxidation reaction of LCV because the absorbance at 410 and 600 nm was changed by the oxidation of LCV, as shown in Fig. 3(a).…”
Section: Resultsmentioning
confidence: 95%
“…38,39) The increase in absorbance at 250 nm is attributed to the generation of C-C double bonds. 40) The change in the absorbance of PVC upon X-ray irradiation was negligible on the coloring due to the oxidation reaction of LCV because the absorbance at 410 and 600 nm was changed by the oxidation of LCV, as shown in Fig. 3(a).…”
Section: Resultsmentioning
confidence: 95%
“…In 1987, Jack Monson studied the winter road non-contact deicing project and designed a microwave deicer. The project failed to be implemented because the deicing efficiency was too low [11,12]. Lindroth Ye et al established the microwave deicing model, designed the microwave deicing test vehicle [13,14], and conducted further research on road microwave deicing technology.…”
Section: Introductionmentioning
confidence: 99%
“…e time of effective deicing area is shortened by 40 seconds. In 2018, Liu et al [13][14][15][16][17] found that the incorporation of iron black into concrete can improve the deicing efficiency and a greater range of deicing, and the microwave heating efficiency was increased by 192% at 15% admixture, but the incorporation of iron black reduced the mechanical properties of concrete. In 2019, Wang et al [18] prepared microwave heated aggregate (MHA) from magnetite and replaced the original aggregate.…”
Section: Introductionmentioning
confidence: 99%